Reversing HIV latency via sphingosine-1-phosphate receptor 1 signaling. (28th November 2017) - Duquenne, Charline; Gimenez, Sandrine; Guigues, Adeline; Viala, Benjamin; Boulouis, Caroline; Mettling, Clément; Maurel, Damien; Campos, Noëlie; Doumazane, Etienne; Comps-Agrar, Laetitia; Tazi, Jamal; Prézeau, Laurent; et al.
Abstract : Objective: In this study, we looked for a new family of latency reversing agents. Design: We searched for G-protein-coupled receptors (GPCR) coexpressed with the C-C chemokine receptor type 5 (CCR5) in primary CD4 + T cells that activate infected cells and boost HIV production. Methods: GPCR coexpression was unveiled by reverse transcriptase-PCR. We used fluorescence resonance energy transfer to analyze the dimerization with CCR5 of the expressed GPCR. Viral entry was measured by flow cytometry, reverse transcription by quantitative PCR, nuclear factor-kappa B translocation by immunofluorescence, long terminal repeat activation using a gene reporter assay and viral production by p24 quantification. Results: Gαi-coupled sphingosine-1-phophate receptor 1 (S1P1) is highly coexpressed with CCR5 on primary CD4 + T cells and dimerizes with it. The presence of S1P1 had major effects neither on viral entry nor on reverse transcription. Yet, S1P1 signaling induced NFκB activation, boosting the expression of the HIV LTR. Consequently, in culture medium containing sphingosine-1-phophate, the presence of S1P1 enhanced the replication of a CCR5−, but also of a CXCR4-using HIV-1 strain. The S1P1 ligand FTY720, a drug used in multiple sclerosis treatment, inhibited HIV-1 productive infection of monocyte-derived dendritic cells and of severe combined immunodeficiency mice engrafted with human peripheral blood mononuclear cells. Conversely, S1P1 agonists were able to force latently infected peripheral blood mononuclear cells and lymph node cells to produce virions in vitro . Conclusion: Altogether these data indicate that the presence of S1P1 facilitates HIV-1 replicative cycle by boosting viral genome transcription, S1P1 antagonists have anti-HIV effects and S1P1 agonists are HIV latency reversing agents.